Caracterização textural e respostas isotópicas U-Pb e Lu-Hf de zircão como indicador petrogenético de granitos pós-colisionais do Orógeno Araçuaí na região centro-sul do Estado do Espírito Santo - Cristina Santos Araujo (2019)
Zircon is widely used to obtain petrogenetic and geochronological information, supporting in the investigation of the evolution of Earth's crust and mantle. With that purpose, a study was carried out focusing on the zircon characterization in samples from three post-collisional plutons of the Araçuaí orogen, located in the south-central region of the Espírito Santo State, Brazil: granites from the Aracê (Pedra Azul) and Vitória plutons, and tonalite from the Mestre Álvaro pluton. Besides a detailed study on zircon morphology and internal structures, we performed in situ U-Th-Pb and Lu-Hf isotopic spot analysis. The remarkable post-collision plutonism (530-480 Ma) of this orogen occurs in association with processes of gravitational collapse and destabilization of the asthenospheric mantle. All together, the post-collisional granites vary from calc-alkaline to shoshonitic, and magnesian to ferroan, including both I-type and A-type granites. Zircon saturation geothermometry in the studied samples indicates temperate for the magmas > 800 °C. Zircons from samples commonly present long-prismatic forms, high Th/U ratio, unzoned to weakly zoned crystals, frequently surrounded by structureless domains of dissolution–recrystallization or thin overgrowth rims. Zircon geochronology resulted in magmatic crystallization ages of 523 ± 2 Ma for the Aracê (Pedra Azul) pluton, 505 ± 1 Ma for the Vitória pluton, and 527 ± 2 Ma for the Mestre Álvaro pluton. Lu-Hf data (Aracê pluton: ƐHf(t) -23.8 to -18.6, TDM 2.47 to 2.25 Ga; Vitória pluton: ƐHf(t) - 10.4 to -7.4, TDM 1.71 to 1.58 Ga; and Mestre Álvaro pluton: ƐHf(t) -8.8 to -0.7, TDM 1.66 to 1.49 Ga) indicate striking crustal involvement in magma genesis. These all features suggest hybrid sources involving mantle and crust, as well as high temperatures of magmatic crystallization. The heat source can be associate with inflow of the asthenospheric mantle due its destabilization after slab breakoff, and an upwelling of a mantle plume in final post-collisional stage of the Araçuaí orogen. The zircons would have crystallized with high cooling rates probably due to a rapid ascent of the magma to a higher crustal level. After the pluton emplacement, zircon changes by in situ dissolution–recrystallization and overgrowth would have occurred in response to interactions with late stage melts at end of magmatic crystallization.